The lncRNA MALAT1 rs619586 G Variant Confers Decreased Susceptibility to Recurrent Miscarriage - Che, Di; Yang, Yanfang; Xu, Yufen; Fang, Zhenzhen; Pi, Lei; Fu, LanYan; Zhou, Huazhong; Tan, Yaqian; Lu, Zhaoliang; Li, Li; Liang, Qihua; Xuan, Qingshan; et al. (Frontiers in Physiology, 2019)
Cardiovascula disease and recurrent miscarriage have shared risk factors, and some cardiovascular disease-related candidate genes have been confirmed to be associated with recurrent miscarriage. Metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) is a long non-coding RNA (lncRNA) that is considered to be associated with susceptibility to cardiovascular disease. However, whether lncRNA MALAT1 polymorphisms are related to recurrent miscarriage susceptibility is unclear. We genotyped three lncRNA MALAT1 polymorphisms (rs591291, rs619586, and rs3200401) in 284 patients and 392 controls using TaqMan methods. Logistic regression was used to evaluate the odds ratios (ORs) and 95% confidence intervals (CIs) adjusted for age. Our results showed that the rs619586 G variant had protective effects against recurrent miscarriage (AG vs. AA: adjusted OR = 0.670, 95% CI = 0.457–0.982, p = 0.040; GG vs. AA: adjusted OR = 0.278, 95% CI = 0.079–0.975, p = 0.046; GG/AG vs. AA adjusted OR = 0.621, 95% CI = 0.429–0.900, p = 0.012). In a combined analyses of protective genotypes, with regard to the three single nucleotide polymorphisms (SNPs), we found that individuals with two or three protective genotypes exhibited a significantly lower risk of recurrent miscarriage than those with no or only one protective genotype (adjusted OR = 0.369, 95% CI = 0.199–0.684, p = 0.002). Moreover, the decrease in recurrent miscarriage risk with two or three protective genotypes was most pronounced in women less than 35 years of age (OR = 0.290, 95% CI = 0.142–0.589, p < 0.001) and in women with 2–3 miscarriages (adjusted OR = 0.270, 95% CI = 0.126–0.580, p < 0.001). In conclusion, our study suggests that the rs619586 G variant may have potential protective effects conferring a decreased risk of recurrent miscarriage in the southern Chinese population.